Solution of the Falkner–Skan Equation Using the Chebyshev Series in Matrix Form - Abdelrady Okasha Elnady; M. Fayek Abd Rabbo; Hani M. Negm (Journal of Engineering)
A numerical method for the solution of the Falkner–Skan equation, which is a nonlinear differential equation, is presented. The method has been derived by truncating the semi-infinite domain of the problem to a finite domain and then expanding the required approximate solution as the elements of the Chebyshev series. Using matrix representation of a function and their derivatives, the problem is reduced to a system of algebraic equations in a simple way. From the computational point of view, the results are in excellent agreement with those presented in published works.